Determinación del perfil lipídico como aporte para el establecimiento de valores de referencia en estudiantes de unidades educativas rurales del Cantón Riobamba - Guamán Paguay, Mayra Patricia (2018)
The objective of this research work is to determine the lipid profile as a contribution to the establishment of reference values in students of rural educational units of the Riobamba canton, in the academic period October 2017 - March 2018. After consulting several bibliographic sources, it was not found a study that specifically determines the reference values of this profile. The types of the research correspond to descriptive, field, cross-sectional, quasi-experimental and qualitative-quantitative process. The technique used was the application of surveys and biochemical tests. This study was carried out in 12 educational units of the sector rural, with a population of 644 students, selecting a sample of 163 students randomly, who voluntarily participated in the application of surveys, prior to signing the informed consent. To carry out the chemical tests of the lipid profile, the automated equipment was used, dimensions ®RxL Max® of the Hospital Provincial General Docente de Riobamba. Lipid profile values were determined in 163 students from the rural area where the result was obtained, in cholesterol an average of 150 mg /dL, in triglycerides a mean of 99 ± 2 mg /dL in HDL cholesterol was 43 ± 3 mg /dL, in LDL cholesterol an average of 77 ± 2 mg /dL. As a result our database can contribute to the reference values since they are within the normal ranges of this profile.